Total Quality Educational Mindset Formation at Muhammadiyah Elementary School Kleco Yogyakarta - Yuliana, Anaas Tri Ridlo Dina (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
The main and fundamental thing to consider in improving the quality of education is to build and form a mindset strategy for all stakeholders of education. This research was conducted by using qualitative descriptive approach. The purpose of this study is to obtain information and describe the formation of total quality educational mindset at Kleco Muhammadiyah Elementary School in Yogyakarta. The formation of the mindset was done through the formulation and the communication of mindset. The formulation of the mindset was done by observing the principals regarding various trends driving the changes that will occur. It then illustrated the impact of changes in the school caused by various efforts of changes that have been observed and formulated by providing the best value for customers, making continuous improvement, and trying to satisfy the needs of stakeholders. The communication mindset that has been formulated was done in two ways, namely through personal behavior and operational behavior. The realization of the result of forming the total quality educational mindset is the formation of member behavior in the organization in accordance with what is expected by the school.